Europäische Union - Vertiefung möglich und nötig? - Lars P. Feld; Christoph M. Schmidt; Isabel Schnabel; Volker Wieland; Sebastian Dullien; Michael Wohlgemuth; Stephan Leibfried; Jörg Philipp Terhechte (Wirtschaftsdienst, 2015)
Mitten in der Griechenland-Krise haben die Präsidenten der fünf wichtigsten europäischen Institutionen Vorschläge für eine weitere Integration der Europäischen Währungsunion unterbreitet. Sie beziehen sich dabei auf die Wirtschafts-, Finanzmarkt- und Bankenunion und gehen sogar so weit, eine Fiskalunion zu skizzieren. Die Autoren diskutieren das 'Juncker-Papier' vor dem Hintergrund der Gefahren einer stärkeren Zentralisierung, der Aufgabe nationaler Souveränität, der demokratischen Legitimation und natürlich der schwierigen Durchsetzbarkeit. – – Discussions about further European integration have intensified since the five presidents published their report to complete the process of European Monetary Union. Four members of the German Council of Economic Experts argue for a mandatory balance of liability and control during each step of European integration, in particular if such steps have budgetary implications for the member states. Other authors view the proposed reforms more positively. They believe that some are useful complements to monetary union, while others lack legal foundations and popular support, which - with respect to the failing confidence of the European citizen - they see as a serious error. An ever closer union among the people of Europe constitutes one of the fundamental goals of the Treaty on European Union. This idea has to be seen in contrast to the current debates concerning the future of the EU, which are dominated by small steps, setbacks or reallocations of competences. Without new ideas and a new institutional design, the European success story could come to an end.
Keywords: E61; E63; F02; H87; 330; Währungsunion; Europäisches Währungssystem; Finanzpolitik; Europäische Integration; EU-Staaten; Meinung